2009
DOI: 10.1007/s10600-009-9275-4
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antimicrobial activity of essential oil from seeds of Anethum graveolens growing in Uzbekistan

Abstract: We have previously studied the chemical composition of essential oil (EO) from seeds of Anethum graveolens from Xinjiang Autonomous District in the PRC [1]. The component composition of essential oils is known to depend on the habitat. It seemed interesting to compare the composition and biological activity of EO from dill seeds growing in China and Uzbekistan. We used GC-MS to establish the structures of the isolated compounds.EO from seeds of A. graveolens (2007 harvest) that were collected in Tashkent Oblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 10 publications
2
14
0
Order By: Relevance
“…In the study by Zeng et al (2011), using the broth microdilution technic (MIC), microbiological and histological technics in mice, demonstrated that dill was active in vitro and in vivo against all the Candida species tested. Yili et al (2009), analyzed the MIC through the Barry method, with an ethylene oxide addition, and they found inhibition results of 0.00273 mg.mL -1 in C. albicans, affirming that the yeast growth, sharply decreased with this component addition in the nutrient medium.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In the study by Zeng et al (2011), using the broth microdilution technic (MIC), microbiological and histological technics in mice, demonstrated that dill was active in vitro and in vivo against all the Candida species tested. Yili et al (2009), analyzed the MIC through the Barry method, with an ethylene oxide addition, and they found inhibition results of 0.00273 mg.mL -1 in C. albicans, affirming that the yeast growth, sharply decreased with this component addition in the nutrient medium.…”
Section: Discussionmentioning
confidence: 87%
“…Elevated concentrations of these constituents and their proportions are of great importance in the product efficacy, confirming their properties and medicals applications. However, studies demonstrated that these isolated compounds don't have the same efficacy of the essential oil (Simões et al, 2010;Yili et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Dill seed essential oil (DSEO) was used early in the last century to treat many pathological conditions, such as disease of the uterus and cervical ectropio, and as an antimicrobial (Editor Committee of National Chinese Medical Manage Bureau, 2005). Some researchers have reported that DSEO possesses anti- C. albicans activity (Yili et al , 2009; Jirovetz et al , 2003; López et al , 2005). Similarly, our laboratory reported that DSEO (from plant material derived from China) is composed of carvone (41.5 %), limonene (32.6 %) and apiol (16.8 %) (Tian et al , 2011), and has anti- Candida activities in vitro and in vivo (Zeng et al , 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The essential oil of Cuminum cyminum L. and Carum carvi L. showed antibacterial activity against various Gram-positive and Gram-negative bacteria (Iacobellis et al 2005). C. albicans and S. aureus growth in plates were inhibited by essential oils of A. graveolens (Yili et al 2009). The essential oil derived from Pyrus salicifolia exhibited antimicrobial activity against S. aureus, Bacillus subtilis, and E. coli (Mamadalieva et al 2018).…”
Section: The Antimicrobial Activity Of Biologically Active Compounds mentioning
confidence: 99%
“…The plant extract of Hypericum perforatum collected from the Chatkal Biosphere Reserve of Uzbekistan demonstrated antagonistic activity against Pseudomonas aeruginosa, E. coli, E. faecalis, K. oxytoca, Klebsiella pneumoniae, and S. aureus (Egamberdieva et al 2013). Yili et al (2009) reported the antimicrobial activity of Anethum graveolens against human pathogens such as Candida albicans and S. aureus. In other studies, Silene wallichiana, Silene viridiflora, and Silene brahuica inhibited several Gram-negative and Gram-positive human pathogenic bacteria (Mamadalieva et al 2008).…”
Section: Medicinal Plants Of Uzbekistan and Their Antimicrobial Activitymentioning
confidence: 99%